2018
DOI: 10.3758/s13421-018-0848-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge revision through the lenses of the three-pronged approach

Abstract: In the present study, we employed the three-pronged approach to determine the actual cognitive processes theorized in knowledge revision. First, the Knowledge Revision Components (KReC) framework was identified as the guiding theory. Second, think-aloud analysis highlighted at which points in refutation texts readers detected discrepancies between their incorrect, commonsense beliefs and the correct beliefs, and the exact processes with which they dealt with these discrepancies-successfully or unsuccessfully, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 81 publications
(101 reference statements)
7
78
1
Order By: Relevance
“…Although the exact nature of how such mechanisms produce the CIE is debated (see Chan et al, 2017;Lewandowsky et al, 2012), theoretical models such as the KReC framework discussed earlier favour the notion of concurrent storage where both the original misinformation and its later correction persist in memory. Both may therefore be candidates for subsequent activation (Gordon, Quadflieg, Brooks, Ecker, & Lewandowsky, 2019; for reviews see Gerrig & O'Brien, 2005;Kendeou et al, 2019;Kendeou, Walsh, Smith & O'Brien, 2014). If negations are indeed encoded as single meaningful units, then concurrent-storage accounts and processes specified by the KReC framework offer a reasonable explanation for the CIE regardless of its polarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact nature of how such mechanisms produce the CIE is debated (see Chan et al, 2017;Lewandowsky et al, 2012), theoretical models such as the KReC framework discussed earlier favour the notion of concurrent storage where both the original misinformation and its later correction persist in memory. Both may therefore be candidates for subsequent activation (Gordon, Quadflieg, Brooks, Ecker, & Lewandowsky, 2019; for reviews see Gerrig & O'Brien, 2005;Kendeou et al, 2019;Kendeou, Walsh, Smith & O'Brien, 2014). If negations are indeed encoded as single meaningful units, then concurrent-storage accounts and processes specified by the KReC framework offer a reasonable explanation for the CIE regardless of its polarity.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is consistent with both previous CIE research as well as theoretical models of knowledge revision. One such model in particular, the Knowledge Revision Components framework (KReC - , for a detailed review see Gerrig & O'Brien, 2005;Kendeou, Butterfuss, Kim & van Boekel, 2019;Kendeou, Walsh, Smith & O'Brien, 2014), assumes that new information encoded into memory (e.g., the correction) has the potential to activate related pieces of information in memory through resonance-based retrieval processes (O'Brien et al, 1998(O'Brien et al, , 2010Rapp & Kendeou, 2009). In this framework, for knowledge revision to succeed, a correction needs to resonate with the initial, corresponding misinformation such that co-activation occurs, triggering conflict detection and subsequent information integration.…”
Section: Polarity and Attitude Effects In The Continued-influence Parmentioning
confidence: 99%
“…Based on this research, several best-practice recommendations have been identified. Specifically, refutations should: (a) come from a trustworthy source (Ecker & Antonio, 2020;Guillory & Geraci, 2013) and, if applicable, discredit the disinformant by exposing their hidden agenda (Walter & Tukachinsky, 2020); (b) make salient the discrepancy between false and factual information, which has been shown to facilitate knowledge revision (Ecker, Hogan, & Lewandowsky, 2017;Kendeou, Butterfuss, Kim, & van Boekel, 2019); (c) explain why the misinformation is false, providing factual information to replace the false information in people's mental models (Paynter et al, 2019;Swire et al, 2017); and (d) draw attention towards any misleading strategies employed by misinformants (Cook et al, 2018;MacFarlane, Hurlstone, & Ecker, 2018, 2020a.…”
Section: Sharingmentioning
confidence: 99%
“…These are brief documents that identify an erroneous belief, refute it, and present several claims that reinforce the best available understanding as a substitute explanation. In doing so, refutation texts promote a specific sequence of cognitive processes theorized to result in knowledge revision (Kendeou et al, 2013(Kendeou et al, , 2014(Kendeou et al, , 2019. Most notably, this includes instigating competitive cognitive conflict between correct and incorrect knowledge that is resolved when misconceptions are overwritten in memory by the quantity and quality of correct supporting explanations.…”
mentioning
confidence: 99%